The Proper Racing Line Brand and the Role of Affiliate Marketing in Boosting Consumer Purchasing Power - Naufal Noor Fadillah; Siti Khumayah; Aghnia Dian Lestari (Indonesian Journal of Advanced Research, 2026)
The development of digital media has encouraged companies to utilize affiliate marketing strategies as part of their marketing communications. In practice, high engagement with promotional content does not always result in a commensurate increase in consumer purchasing power. This study aims to analyze the role of affiliate marketing in increasing consumer purchasing power for the Proper Racing Line brand through the dimensions of affiliate credibility, promotional content quality, and relationship management. The study employed a descriptive qualitative method with data collection techniques consisting of in-depth interviews and documentation. The research informants comprised internal staff of Proper Racing Line, affiliates, and consumers selected using purposive sampling. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. The results indicate that affiliate credibility is a key factor in building consumer trust in the promoted products. Additionally, promotional content that is informative, educational, and showcases firsthand product usage experiences helps consumers understand the product’s benefits before making a purchase. The relationship established between the brand and the affiliate through ongoing communication also plays a role in maintaining the consistency of the information received by consumers. This study concludes that consumer purchasing power is influenced not only by high engagement on social media but also by the level of trust in the affiliate, the quality of the information conveyed, and the relationship built among the brand, the affiliate, and the consumer in affiliate marketing activities.